Nutritional Status and Dietary Management According to Hemodialysis Duration - Lim, Hee-Sook (Clin Nutr Res, 2019)
As the incidence of chronic diseases such as diabetes and hypertension increases, complications such as decreased renal function are also increasing in many patients. Nutritional management in hemodialysis patients is a very important factor for prognosis and quality of life. The purpose of this study was to investigate the differences in nutritional status and dietary management according to hemodialysis duration. A total of 145 patients were divided into 4 groups according to hemodialysis duration: less 1 year (D1), 1–5 years (D2), and above 5 years (D3). The rates of protein-energy wasting were 31.1% in D1 group, 49.5% in D2 group, and 47.6% in D3 group. However, there was no significant difference between the 3 groups. Nutrient intake analysis showed that protein, iron, and vitamin C were significantly lower in the D3 group than in the D1 group. Protein intake in all 3 groups was insufficient compared to the recommended dietary amount for dialysis patients. The most difficult aspect in dietary management was cooking with low sodium. In the D3 group, which had the longest duration of dialysis, the practice of diet therapy and self-perceived need for nutrition education was lowest. Observations of nutritional status are necessary to maintain the health status of dialysis patients. In addition, education plans should be prepared to mediate the nutrient intakes and identify the patient's difficulties and provide practical help.